Augmentation of neutral sodium chloride absorption by increased flow rate in rat ileum in vivo. - Harris, M S (1986)
Studies in intact animals have shown that intestinal solute absorption is enhanced with increasing flow rates; the mechanism of this phenomenon has not been explored in detail. We used single pass perfusions of rat ileum to study the effect of higher flow rate on electrolyte absorption. Augmenting perfusion rate from 0.5 to 5.0 ml/min resulted in increased rates of sodium (11.0 +/- 0.9 vs. 23.5 +/- 2.7 mueq/min X g) and chloride (12.1 +/- 0.8 vs. 25.0 +/- 2.2 mueq/min X g) absorption, reduction in the estimated unstirred layer thickness (668 +/- 31 vs. 433 +/- 28 micron), minimal changes in intraluminal pressure and transmural potential difference, and a small, though significant, increase in intraluminal volume (19.4 +/- 8.4%). Removal of sodium from the perfusion medium abolished the effect of increased flow rate on chloride absorption as did removal of chloride on sodium absorption; addition of furosemide or acetazolamide to Ringer's solution also inhibited this effect. In separate experiments, stepwise increases in intraluminal volume were induced by elevating the outflow tubing; no effect on electrolyte transport was observed. These studies demonstrate that neutral sodium chloride absorption is enhanced in rat ileum at higher flow rates, perhaps as a result of a decrease in the thickness of unstirred layers.